Scrotal ultrasonography: should it be used in routine evaluation of infertile men? - Onur, M. R.; Firdolas, F.; Onur, R.; Kocakoc, E.; Akpolat, N.; Orhan, I. (Wiley, 2008)
Several studies have suggested that male infertility and testicular cancer may have common aetiological factors. Scrotal ultrasonography (US) has an important role in the diagnosis of testicular tumours when not palpable by physical examination. In this study, we present two infertile men referred to our clinic. Patients were evaluated by a detailed physical examination, semen analyses and hormonal assessment. Both patients underwent scrotal US examination. Semen analysis of the patients revealed oligoasthenospermia in both patients. Scrotal US revealed hypoechoic masses in the left and right testes of both patients, which were nonpalpable by physical examination. Scrotal exploration and subsequent orchidectomy were performed. Histopathological examination revealed mixed germ cell tumour and Sertoli-Leydig cell tumour in case 1 and case 2 respectively. With these cases, we discussed the role of scrotal US in the routine diagnostic evaluation of infertile men.
Keywords: infertility; scrotal ultrasonography; semen analysis; testis cancer